Social Science's Need for a Cultural Symbols Paradigm - Mahmoud Dhaouadi (International Institute of Islamic Thought, 2002)
The thesis of this paper is that human beings are remarkably distinct from other living beings (animals, birds, insects, etc.) and Artificial Jntelligence (Al) machines (computers, robots, etc.) by what we would like to call cultural symbols. The latter refers to such cultural components as language, science, knowledge, religious beliefs, thought, myths, cultural norms and values.